Electricity Switch Using Internet Of Things (Iot) - Sabam Parjuangan; Nurfiana Nurfiana; Dodi Yudo Setyawan; Arif Sofiyan (Proceeding International Conference on Information Technology and Business, 2019)
The problem of a fixed power switch or is only in a controlled device, has its own problems.The problem is if you forget to turn off, or cannot turn off because there are certain activities that cannot be abandoned. The basic of these problems, it is necessary to present a solution. The solution in question is an electric switch that can be controlled remotely and can be controlled with a variety of devices. This discovery presents a solution to the problem of a fixed electric switch. By utilizing qualified communication network, integrated with web technology as a user interface and a device that can be used to control devices through the internet network, the node MCU is integrated with a relay. The test results show that the electric switch which is controlled remotely by a web page running well and is constant. This finding is given the name internet of things (IoT) electricity switch.Keywords: Switch, Electricity, Internet of Things, Web, Node MCU.